Catarata senil: Características e percepções de pacientes atendidos em projeto comunitário de reabilitação visual - Temporini, Edméa Rita; Kara-josé, Newton; Kara-josé, Newton [UNESP] (Conselho Brasileiro de Oftalmologia, 1997)
A survey was conducted to identify some patients' characteristics and perceptions related to senile cataract and delivery of cataract care. The patients were diagnosed by means of ophthalmic examination carried out on a cataract-free-zone project performed within a defined geographic area in Brazil. A questionnaire was administered by interviewing 339 subjects, who presented the following characteristics: 51.9% were males and 48.1% were females; ages varying between 50 and 94 years; 55.7% have not gone to school; 73.7% have stopped working. The overuse of eyes during work (43.1%) and age itself (40.7%) were referred by them as the main causes of their cataract. Financial reasons were mainly pointed out to explain their non-previous ophthalmic examination. Approximately 40.0% were freightened about cataract surgery in account of blindness or death; 41.4% of the subjects declared that blindness was due to God's will. We recommend eye health educational programs for prevention of blindness and sight restoration.

Realizou-se um survey com o propósito de identificar características e percepções de portadores de catarata senil em relação à doença e à assistência oftalmológica. Foram entrevistados 339 pacientes identificados pelo Projeto Catarata em Mogi-Guaçu (Brasil). Apresentaram as seguintes características: 51,9% do sexo masculino e 48,1% do sexo feminino, idades entre 50 e 94 anos, 55,7% nunca freqüentaram escola e 73,7% não mais exerciam atividades profissionais. Atribuíram ao uso dos olhos no trabalho (43,1%) e à velhice (40,7%) sua dificuldade visual. As razões declaradas da ausência de tratamento oftalmológico anterior foram principalmente financeiras. Aproximadamente 40,0% declararam ter medo da cirurgia de catarata, por recearem cegueira ou morte; 41,4% atribuíram a cegueira ao desígnio divino. Enfatizase a necessidade de ações educativas em saúde ocular e maior facilidade de acesso ao tratamento para prevenção da cegueira e reabilitação visual.
Senile cataract: Patients' characteristics and perceptions identified on a sight restoration communitary project
Keywords: blindness prevention; senile cataract; patients' perceptions; Prevenção da cegueira; Catarata senil; Percepção de pacientes